Impact of high-rise building shapes on wind flow characteristics and energy potential - Mokhtari, Ehsan (2022)
This research project aims to study the design of high-rise buildings and investigate how wind affects energy absorption by developing an aerodynamic optimization procedure (AOP) and using Computational Fluid Dynamics (CFD) in COMSOL Multiphysics. The goal of the study is to optimize building shape for wind energy exploitation. The electricity sector is a significant source of carbon dioxide emissions and contributes to global climate change. Wind energy has become a potential source of low-carbon energy production in recent years. The shape of buildings is a significant factor in aerodynamics, providing an opportunity for wind power control and wind energy proliferation. In a smart sustainable city, building costs can be reduced without affecting structural elements. By optimizing building shape in the early stages of design, it is possible to control wind-induced loads and responses, as well as reduce energy demand in high-rise buildings where resource consumption is higher than in low-height buildings. The research includes four case studies with the same height but different cross-section plans (circular and rectangular), and analyzed based on wind velocity maximization. The study used three-dimensional CFD simulation of wind loading on tall buildings to optimize building shape. The results showed an improved performance of circular models compared to rectangular models in terms of aerodynamic characteristics. The corner modification in buildings could be an asset for generating potential electricity by incorporating wind turbines. The validation procedure is primarily achieved from the development of a robust technique of inflow generation, called Air Flow over an Ahmed Body, which will be used to generate the wind velocity field in the simulation. The accomplished research generally offers progress in numerical techniques of climate responsive design, improving the urban built environment in terms of resilience and sustainability. The research will provide valuable insights for architects, engineers, and building developers to design and optimize high-rise buildings for wind energy exploitation, reducing the carbon footprint and improve the energy efficiency of the building.